Talar Morphometry - A Study in West Bengal Population with Literature Review - Ananya Biswas; Hironmoy Roy; Arnab Bhar; Anwesa Pal; Indra Datta (Al Ameen Medical College, 2022)
Background: Talus, one of the seven tarsal bones, has been topic of interest for anatomist, anthropologist and forensic-medicine for several years. It has been considered as an important bone for locomotor function. Till date few anthropometric data is available from the eastern India specifically from Bengal. Objective: Measurement of different morphometric parameters of dry human tali from West Bengal. Methods: In the present study authors measured different parameters in 100 available tali in Anatomy Departments of different medical colleges of Kolkata over last six months. Measurement of length, width, height, trochlear-length of talus and length, width and depth of sulcus tali were taken by slide-calipers. Result: Present study revealed mean values of length 53.37 ± 3.69 mm, width 38.62 ± 2.91 mm, height 30.85 ± 4.11 mm, trochlear length 33.48 ± 3.58 mm, length of sulcus tali 29.27 ± 3.91 mm, width of sulcus tali 15.49 ± 3.13 and depth of sulcus tali 6.23 ± 1.04 mm. Conclusion: Measurement of different parameters of talus can be useful for surgical intervention, prosthetic invention, medico-legal aspect and in anthropometry. In addition to the anthropometric data available for population from other zones of India, this study adds the data from Eastern India.